Konsep Bahagia Menurut Hamka: Analisis Studi Pemikiran Psikologi Islam - Indallah, Sayyid Muhammad; Ilhami, Muhammad Azfa Akbar (Institute of Research and Public Service Universitas Jenderal Soedirman, 2023)
In this modern era, which is influenced by Western thought patterns, it is necessary to sift and select what aligns with Islamic teachings. Furthermore, in this modern etiquette, there is no authority of knowledge or what is referred to as secularization, hence the absence of a scientific authority as the measure of truth today. The purpose of this research is to elucidate Hamka's modern Sufism concept to address the issues of modernism and secularization with a contemporary understanding of Sufism. In composing this manuscript, the author employs a descriptive-analytical method to explain Hamka's concept of Sufism, with an analysis involving other prominent figures. The findings of this research can be summarized as follows: Sufism is understood as a doctrine about the means and teachings to attain true happiness and glory, which is the ma'rifatullah or the knowledge of Allah. Additionally, there is a method to achieve genuine happiness and glory, which is through religion, comprising elements of belief, faith, and perfection in one's religious practice. Furthermore, there are stages to attain this, primarily through reason, as a person's glory or happiness is measured by the degree of their intellectual capacity. Ultimately, true happiness is the ma'rifatullah or the knowledge of Allah. Therefore, Hamka explains that there are levels of happiness, namely temporary happiness and genuine happiness, and genuine happiness is the ma'rifatullah achieved through the perfection of intellect and wisdom.